Direct Connection Between Auroral Oval Streamers/Flow Channels and Equatorward Traveling Ionospheric Disturbances - Lyons, Larry R.; Nishimura, Yukitoshi; Zhang, Shunrong; Coster, Anthea; Liu, Jiang; Bristow, William A.; Reimer, Ashton S.; Varney, Roger H.; Hampton, Don L. (Frontiers in Astronomy and Space Sciences, 2021)
We use simultaneous auroral imaging, radar flows, and total electron content (TEC) measurements over Alaska to examine whether there is a direct connection of large-scale traveling ionospheric disturbances (LSTIDs) to auroral streamers and associated flow channels having significant ground magnetic decreases. Auroral observations allow identification of streamers and TEC observations detect ionization enhancements associated with streamer electron precipitation. Radar observations allow direct detection of flow channels. The TEC observations show direct connection of streamers to TIDs propagating equatorward from the equatorward boundary of the auroral oval. The TIDs are also distinguished from the streamers to which they connect by their wave-like TEC fluctuations moving more slowly equatorward than do the TEC enhancements from streamer electron precipitation. TIDs previously observed propagating equatorward from the auroral oval have been identified as LSTIDs. Thus, the TIDs here are likely LSTIDs, but we lack sufficient TEC coverage necessary to demonstrate that they are indeed large scale. Furthermore, each of our events show TIDs’ connection to groups of a few streamers and flow channels over a period on the order of 15 min and a longitude range of ~10-15o, and not to single streamers. (Groups of streamers are common during substorms. However, it is not currently known if streamers and associated flow channels typically occur in such groups.) We also find evidence that a flow channel must lead to a sufficiently large ionospheric current for it to lead to a detectable LSTID, a few tens of nT ground magnetic field decrease being not sufficient.